Water and sanitation hygiene in South Sudan: What needs to be done to bridge the gap? - Victor Vuni Joseph (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2014)
Water, and sanitation hygiene (WASH) is a major public health challenge, not only globally, but also in the Republic of South Sudan. It is estimated that 1 in 10 (768 million) of the world's population do not have access to safe drinking water, most of whom are in developing countries, while a third of the world's population (2.5 billion people) do not have access to adequate sanitation